Impact of ICT on Library and Information Science: Major Shifts and Practices in CUSAT Central Library - Santha Devi Antherjanam N K Sheeja (International CALIBER-2008, 2008)
Information is knowledge, facts or data. For the purpose of enabling the users to assimilate information, it should be repacked. Knowledge becomes information when it is externalized i.e. put in to the process of communication. The effectiveness of communication technology depends how well it provides its clients with information rapidly, economically and authentically. A large number of ICT enabled services including OPAC; e-resources etc. are available in the university library. Studies have been done to find the impact of ICT on different sections of CUSAT library by observing the activities of different sections; discussions with colleagues and visitors; and analyzing the entries in the library records. The results of the studies are presented here in the form of a paper.